Metabolic engineering of plant biomass production of biofuel - Borisjuk, N.V.; Andrianov, V.; Pogrebnyak, N.; Brinker, A.; Dixon, J.; Flynn, J.; Matyszczuk, P.; Andryszak, K.; Laurelli, M.; Spitsin, S.; Golovkin, M.; Koprowski, H. (Фактори експериментальної еволюції організмів, 2010)
Tobacco plants engineered to constitutively overexpress DGAT, a key enzyme in
plant lipid biosynthesis, or to inducibly express a transcription factor LEC2 that govern
seed maturation, have about two-fold increase in total fatty acid content in their green
biomass. The increased fatty acid content was accompanied by changes in their composition that favor development of tobacco as a renewable source of biofuel.